THE EFFECTIVENESS OF INTEGRATING PROFESSIONAL MILITARY CONTEXTS INTO ENGLISH LANGUAGE LEARNING - Shiknazarova Durdona Baxtiyarovna (Modern American Journals, 2025)
This article investigates the effectiveness of integrating professional military contexts into English language learning for future officers. The study emphasizes how context-based instruction enhances cadets’ communicative competence, particularly in speaking and listening skills required in military environments. By embedding authentic military scenarios, terminologies, and problem-solving tasks into the curriculum, learners are better prepared for real-life communication challenges. The research highlights the role of integrated methods such as task-based learning, problem-based learning, and ICT tools, which create meaningful connections between language knowledge and professional application. Findings suggest that incorporating professional contexts fosters learner motivation, improves retention of specialized vocabulary, and develops cross-cultural awareness necessary for international military cooperation. The article concludes that integrated approaches significantly contribute to both linguistic and pragmatic competence, thus providing cadets with effective tools for communication in military-specific domains.
Keywords: Communicative competence, military cadets, integrated method, English language, professional context, task-based learning, motivation.